1999
DOI: 10.1023/a:1005219227668
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Twenty each of healthy lactating Friesian and Holstein cows were studied. They were of similar age and body weight, nonpregnant in their third lactation and 80-100 days post partum. The investigation was carried out for 8 weeks on two farms at the same time during the hot summer season in Egypt. The first farm was in Demietta (North east of the Nile Delta, 31 degrees 40' N) on 20 Friesian cows and the second was in Fakous (East of the Nile Delta, 30 degrees 40' N) on 20 Holstein cows. On each of the two farms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…Heart rate is a physiological response to stress due to adrenal stimulation and consequent rise in serum adrenaline and noradrenaline levels 33 . This response also increases during heat stress, especially when animals are raised in the tropics, but also in situations as fear, excitement, and physical exercise 13 , 32 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate is a physiological response to stress due to adrenal stimulation and consequent rise in serum adrenaline and noradrenaline levels 33 . This response also increases during heat stress, especially when animals are raised in the tropics, but also in situations as fear, excitement, and physical exercise 13 , 32 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The GPT gene encodes glutamicpyruvate transaminase. Habeeb et al [36] conducted a study comparing the physiological and biochemical changes in Egyptian native cows and introduced cows under hot summer conditions, finding that serum levels of glutamate aminotransferase were significantly higher in native cows than in introduced cows under hot conditions, suggesting that the GPT gene may be associated with heat stress in dairy cows. The PYCR3 gene encodes a protein belonging to the pyrroline-5-carboxylic acid reductase family, which has been shown to be involved in genotoxic, inflammatory, and oxidative stress responses [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, the factors such as species, numbers and age of animal besides environmental aspects will serve a significant role in the rate of infection (Emanabdeen 2018). Furthermore, a study conducted by Marai et al (1999) showed that the rate of ringworm infection among cattle higher in foreign breed than in native breed. According to studies conducted by Pascoe (1979) and Shams et al (2009) the prevalence rate was higher in the young animals.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%